2014
DOI: 10.1016/j.rehab.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the medical causes of death in cerebral palsy

Abstract: These results concur with other published data, i.e. subjects with cerebral palsy die younger than the French general population, and the principal causes of death are respiratory and circulatory problems. This study emphasises the importance of access to epidemiological data about the French cerebral palsy population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 18 publications
1
50
1
Order By: Relevance
“…117 Similarly, in a cohort study of 341 adults with CP in London, a higher percentage of deaths due to respiratory diseases was reported among young adults with CP compared with adults without CP. A descriptive cross-sectional study conducted in France found that the percentage of deaths due to respiratory diseases was higher among adults with CP, but the percentage of deaths due to diseases of the circulatory system and neoplasms was lower.…”
Section: Reviewmentioning
confidence: 93%
“…117 Similarly, in a cohort study of 341 adults with CP in London, a higher percentage of deaths due to respiratory diseases was reported among young adults with CP compared with adults without CP. A descriptive cross-sectional study conducted in France found that the percentage of deaths due to respiratory diseases was higher among adults with CP, but the percentage of deaths due to diseases of the circulatory system and neoplasms was lower.…”
Section: Reviewmentioning
confidence: 93%
“…This is important, because despite being weakened, the FM of CP patients may be similar to normal, by proportional decrease of body weight components 39 . The main cause of morbidity and mortality were respiratory infections in our study, according to what was published 4,33 . These patients have an increased risk of pulmonary aspiration, secondary to the coexistence of GER and dysphagia 6 , and the presence of WB is an independent risk factor for recurrence of hospitalizations 34 .…”
Section: Discussionmentioning
confidence: 58%
“…Most studies comparing individuals with CP to the general population have focused on differences in mortality (Duruflé-Tapin et al, 2014), Adults with Cerebral Palsy physical health issues (Day et al, 2007;Jahnsen, Villien, Aamodt, Stanghelle, & Holm, 2004;Jahnsen, Villien, Stanghelle, & Holm, 2003;Liptak et al, 2001), and patterns of health service use (Young et al, 2006(Young et al, , 2007(Young et al, , 2011. In terms of mortality, because of their complex medical and physical health issues, individuals with CP tend to die at a younger age than the general population (Duruflé-Tapin et al, 2014). Compared to the general population, individuals with CP across all ages, also tend to use health services more often (Young et al, 2006(Young et al, , 2007(Young et al, , 2011.…”
Section: Adults With Cp and The General Populationmentioning
confidence: 99%